LInking EDCs in maternal Nutrition to Child health (LINC study) - protocol for prospective cohort to study early life exposure to environmental chemicals and child health - Marijke de Cock; Ilona Quaak; Eva J. Sugeng; Juliette Legler; Margot van de Bor (BMC, 2016)
Abstract Background The presence of chemicals in the environment is ubiquitous. Human biomonitoring studies have shown that various chemicals can be detected in the majority of the population, including pregnant women. These compounds may pass the placenta, and reach the fetus. This early life exposure in particular may be detrimental as some chemicals may disrupt the endocrine system, which is involved in various processes during development. The LINC study is a prospective birth cohort designed to study associations between early life environmental exposures and child health, including growth and neurodevelopment. The purpose of this paper is to give an overview of this cohort. Methods and design Recruitment for this cohort has started in 2011 in three Dutch areas and is still ongoing. To date over 300 mother-child pairs have been included. Women are preferably included during the first trimester of pregnancy. Major congenital anomalies and twin births are reasons for exclusion. To assess exposure to environmental chemicals, cord blood, placenta, meconium and vernix are collected. Parents collect urine of the child shortly after birth and breast milk in the second month of life. Exposure to a broad range of environmental chemicals are determined in cord plasma and breast milk. Furthermore various hormones, including leptin and cortisone, are determined in cord plasma, and in heel prick blood spots (thyroxine). Data on anthropometry of the child is collected through midwives and youth health care centres on various time points until the child is 18 months of age. Furthermore cognitive development is monitored by means of the van Wiechen scheme, and information on behavioral development is collected by means of the infant behavior questionnaire and the child behavior checklist. When the child is 12 months of age, a house visit is scheduled to assess various housing characteristics, as well as hand-to-mouth behavior of the child. At this visit exposure of the child to flame retardants (with endocrine disrupting properties) in house dust is determined by means of body wipes. They are furthermore also measured in a saliva sample of the child. Next to these measurements, women receive questionnaires each trimester regarding amongst others lifestyle of the parents, general health of the parents and the child, and mental state of the mother. Discussion This study was approved by the medical ethics committee of the VU University Medical Centre. Consent for the infant is given by the mother, who is specifically required to give consent for both herself as well as her child. Results will be published regardless of the findings of this study, and will be widely disseminated among related medical stakeholders (e.g. midwives and pediatricians), policy makers, and the general public.